2015
DOI: 10.1073/pnas.1517326112
|View full text |Cite
|
Sign up to set email alerts
|

LSD1/KDM1A promotes hematopoietic commitment of hemangioblasts through downregulation of Etv2

Abstract: The hemangioblast is a progenitor cell with the capacity to give rise to both hematopoietic and endothelial progenitors. Currently, the regulatory mechanisms underlying hemangioblast formation are being elucidated, whereas those controllers for the selection of hematopoietic or endothelial fates still remain a mystery. To answer these questions, we screened for zebrafish mutants that have defects in the hemangioblast expression of Gata1, which is never expressed in endothelial progenitors. One of the isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 69 publications
1
48
0
Order By: Relevance
“…Therefore, by directly maintaining the expression of key players in the OEP module (Sox8, Pax2, Etv4 and Zbtb16) that precede its own expression, Lsd1 becomes part of a sub-network that acts like a central hub for the entire ear cascade. Interestingly, these Lsd1 targets are dependent on FGF signalling for their initial expression, and Lsd1 is known to regulate both Wnt and FGF signalling pathways (Chen et al, 2016;He et al, 2016;Huang et al, 2017Huang et al, , 2013Lei et al, 2015;Takeuchi et al, 2015).…”
Section: Lsd1 Maintains the Oep Module At The Top Of The Inner Ear Rementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, by directly maintaining the expression of key players in the OEP module (Sox8, Pax2, Etv4 and Zbtb16) that precede its own expression, Lsd1 becomes part of a sub-network that acts like a central hub for the entire ear cascade. Interestingly, these Lsd1 targets are dependent on FGF signalling for their initial expression, and Lsd1 is known to regulate both Wnt and FGF signalling pathways (Chen et al, 2016;He et al, 2016;Huang et al, 2017Huang et al, , 2013Lei et al, 2015;Takeuchi et al, 2015).…”
Section: Lsd1 Maintains the Oep Module At The Top Of The Inner Ear Rementioning
confidence: 99%
“…In the zebrafish lateral line, Lsd1 is required to activate Etv4, Axin2 and Tcf7l2 to promote supporting cell proliferation upon hair cell damage (He et al, 2016), whereas it downregulates Etv2 to promote commitment of hematopoietic progenitor cells to their fate (Takeuchi et al, 2015). Furthermore, in cancer cells, Lsd1 promotes the Wnt pathway by repressing negative regulators of Wnt/β-catenin signalling such as APC, Prickle, Sfrp5 and Dkk1 (Huang et al, 2017(Huang et al, , 2013Lei et al, 2015).…”
Section: Lsd1 Maintains the Oep Module At The Top Of The Inner Ear Rementioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression analysis by quantitative polymerase chain reaction showed expression of human hemoglobin beta and hemoglobin gamma, confirming the erythroid nature of the generated human cells (Figure 4F). The expression levels of hematopoietic transcriptional factors – RUNX1 and PU.1 , as well as the erythroblast transcription factor GATA1 , 24,25 were also markedly enhanced when compared with fibroblasts (Figure 4G). Moreover, erythroid colony-forming-cell assay demonstrated formation of distinct erythroid colonies (Figure 4H and 4I).…”
Section: Resultsmentioning
confidence: 98%
“…Further studies revealed an indispensable role for Kdm1a, in the context of Gfi-1/1b, for the emergence of HSCs from the AGM through silencing the endothelial program within the HE both in mice and zebrafish (13, 14), suggesting an evolutionary conserved role in definitive hematopoiesis. Conditional deletion of Kdm1a in fetal ( Vav1 Cre ) and adult ( Mx1 Cre ) HSPCs resulted in severe pancytopenia and compromised terminal differentiation of granulocytic and erythroid lineages (15, 16).…”
Section: Introductionmentioning
confidence: 98%